DAMPAK SOSIAL PARIWISATA DI KAMPUNG TURIS PRAWIROTAMAN: SEBUAH KAJIAN LITERATUR - Eko Sugiarto (Pringgitan, 2021)
This research is a literature study with the theme of the tourism social impact in a village, namely Prawirotaman Village in Yogyakarta. There are two questions to be answered in this research, those are (1) how the origin of the name Prawirotaman as a "tourist village"?; and (2) what social impacts arise from tourists in Kampung Prawirotaman as a "tourist village"? The data in this research was collected from the results of previous researches. The conclusions of this research show that the emergence of Prawirotaman as a "tourist village" needs a quite long process and has social impacts, such as (1) profession changing that bring up new social statuses; (2) social relation changing in certain circles, especially related to inter-individual marriage and job; (3) availability of job vacancies that attract newcomers and cause unfair competition; and (4) new pattern of social interaction. As a note, this research is made by the previous research data through literature studies because it was conducted during the Covid-19 pandemic which made it impossible to conduct direct interviews and observations. Therefore, further research needs to be done related to the same theme in Prawirotaman using primary data, through observation and in-depth interviews, so that it can complete the shortcomings that have not been accommodated in this article and also making the data presented more up to date.Keywords: Social Impact, Tourism, Tourist Village